2017
DOI: 10.1063/1674-0068/30/cjcp1607143
|View full text |Cite
|
Sign up to set email alerts
|

High Resolution Synchrotron Diffraction Study on Charge Density Distribution of Ampicillin Trihydrate

Abstract: Charge density distribution in ampicillin trihydrate was investigated experimentally. Results were compared with the quantum calculations using density functional theory. The charge derived properties including Mulliken atomic charges, dipole moment, and molecular electrostatic potential were calculated. The multipole analysis was done for the refinement of experimental population parameters. The structure factors obtained from multipole treatment were used for the construction of Fourier maps. Topological pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…The asymmetry in this stable ampicillin monomer charge distribution owing to the presence of primary -NH 2 and -C = O, results in the generation of a net interfacial dipole with a large magnitude of 30.28 Debye. 21,22 This ampicillin's dipole was found to be many orders higher than other amine-based molecules ( Supplementary Fig. 3) such as PEI, which has a dipole of 1.3 Debye.…”
Section: Concentration-dependent Chemical Interactions Of Ampicillinmentioning
confidence: 85%
See 1 more Smart Citation
“…The asymmetry in this stable ampicillin monomer charge distribution owing to the presence of primary -NH 2 and -C = O, results in the generation of a net interfacial dipole with a large magnitude of 30.28 Debye. 21,22 This ampicillin's dipole was found to be many orders higher than other amine-based molecules ( Supplementary Fig. 3) such as PEI, which has a dipole of 1.3 Debye.…”
Section: Concentration-dependent Chemical Interactions Of Ampicillinmentioning
confidence: 85%
“…Even though, most research on optoelectronic devices demonstrated vertical (orthogonal) dipole formation; [18][19][20] the spatial orientation of the generated horizontal (or inclined) interfacial dipole in ampicillin molecule with respect to changes in pH was recently simulated by Malloci et al 21 The primary, secondary, and tertiary (cyclic amide in lactam ring) amine along with the carbonyl group (-C = O) present in ampicillin's structure provide a specific charge distribution over the molecule. 21 This resulted in an interfacial dipole with a larger magnitude (30.28 Debye) 21,22 as compared with the dipole from other amine-based molecules such as polyethyleneimine (PEI) (1.3 Debye) 23 and even penicillin (5.99 Debye). 24 The utilization of amine-based molecules including biomaterials and amino acids have been previously reported to alter the work function (φ) of the layers/substrates owing to the generation of interfacial dipole for various optoelectronic and OPV applications.…”
mentioning
confidence: 99%